Assessment of Fundamental Movement Skills in Childhood Cancer Patients. Issue 12 (30th July 2015) - Naumann, Fiona L.; Hunt, Mitchel; Ali, Dulfikar; Wakefield, Claire E.; Moultrie, Kevin; Cohn, Richard J.
<x xml:space="preserve">Abstract</x> Background The improved treatment protocols and subsequent improved survival rates among childhood cancer patients have shifted the focus toward the long‐term consequences arising from cancer treatment. Children who have completed cancer treatment are at a greater risk of delayed development, diminished functioning, disability, compromised fundamental movement skill (FMS) attainment, and long‐term chronic health conditions. The aim of the study was to compare FMS of childhood cancer patients with an aged matched healthy reference group. Methods Pediatric cancer patients aged 5–8 years (n = 26; median age 6.91 years), who completed cancer treatment (<5 years) at the Sydney Children's Hospital, were assessed performing seven key FMS: sprint, side gallop, vertical jump, catch, over‐arm throw, kick, and leap. Results were compared to the reference group (n = 430; 6.56 years). Results Childhood cancer patients scored significantly lower on three out of seven FMS tests when compared to the reference group. These results equated to a significantly lower overall score for FMS. Conclusions This study highlighted the significant deficits in FMS within pediatric patients having completed cancer treatment. In order to reduce the occurrence of significant FMS deficits in this population, FMS interventions may be warranted to assist in recovery from childhood cancer, prevent late effects, and improve the quality of life in survivors of childhood cancer. Pediatr Blood Cancer 2015; 9999:XX–XX © 2015 Wiley Periodicals, Inc.